Can PCV be used as an indicator of trypanosomiasis and production level in cattle? - Feron, A.; D'Ieteren, G.D.M.; Itty, P.; Maehl, H.M.; Mulungo, M.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Sheria, M.; Thorpe, W.R.; Trail, J.C.M. (OAU/STRC, 1988)
Results of a study conducted to estimate the importance of factors influencing blood packed cell volume (PCV) and to investigate possible relationships between PCV and reproductive & liveweight performance of N'Dama cattle exposed and not exposed to trypanosomiasis under the same system of management on two ranches in Zaire